FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI MODERATING VARIABEL - Leni Deli., Ade Fatma Firman Syarif (Jurnal Riset Akuntansi dan Bisnis, 2015)
This study was made to test and prove empirically about the influence of of competency, independency and auditor experience to audit quality wich is moderated by auditor ethic. This study is quantitative study witch causal associative approach. Survey method was used by giving questionnaires to the auditors whowork in public accounting office in Medan. Non-probability sampling was chosen to by 61 persons as sample. The Data was analyzed by mutiple regresion and Moderated Regression Analysis (MRA). The results showed that simultane ouslythere was positive effect and significant competency, independency and auditorexperience to the audit quality. Beside, partialy or base on t test positive effect and significant was found between competency and independency to audit quality. But,working experience was negative not significant to audit quality. This study also found that auditor ethic could not moderated the competency influence, independency, and audit quality to working experince. For the further study it suggested to use other moderation variable wich is possibly give influence to competency, independency and auditor experience to audit quality.